Family Problems in Couples Of Different Community Organizations Case Study In Batu Sopang District - Fauziah Hayati, MHI; Lisa Irmatillah (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2023)
The background of this research is that there are married couples who are divorced due to differences in social organization in the household. Due to differences in understanding from the organization itself, this couple faces problems in their household. This study aims to find out how family problems are in couples with different social organizations in Batu Sopang District. This type of research is empirical research (field research) which uses a qualitative approach and produces descriptive data and is located in Batu Sopang District. Data collection techniques through structured interviews (interview). The research results were processed using editing, classification, and matrixation techniques, then analyzed descriptively qualitatively with reference to the theoretical basis. The results of research on family problems in this problem are caused by disputes that occur up to divorce, the participation of parents in children's homes, this problem occurs because of poor communication, parents who are too involved in their children's household affairs can cause problems that have an impact on household harmony child. So to overcome this problem, several things should be done, such as discussing the problems that occur in the household and as much as possible if there is no divorce, because basically God really hates divorce.